Tinjauan Aspek Ekonomi dan Strategi Implementasi Pengelolaan Sumber Daya Hutan Berkelanjutan di Kabupaten Sidrap - Dahlan Dahlan; Nurdin Dalya; Afriyani Afriyani; Tri Sulkarnain Ahmad (Al-Buhuts, 2021)
How to actually manage natural resources that provide maximum welfare for the community is an important question that we try to uncover through this research. Management of natural resources, especially forestry in Sidrap Regency is based on the wealth of forest resources which is relatively small compared to other districts in South Sulawesi, which is only 1.8% of the total forest area of ​​South Sulawesi. However, the forest area has an important meaning for the people of Sidrap Regency and the surrounding areas because from an area of ​​188,325 ha, there is a forest area of ​​68,810.8 ha or about 36.5% of the total area. The research locations are villages representing forest conditions in the eastern part (Latimojong Forest Complex) and those representing the western part (Nepo-nepo Forest Complex) Sidrap Regency. The units of analysis in this study are: community groups that are directly involved in forest management activities, namely community leaders, traditional leaders, religious leaders and environmentalists and community groups that are not directly involved in forest management, namely DPRD members, youth leaders and NGOs. Information was collected through the contemplation process of the community who knew the concepts and practices of forest management expressed by the informants. The review of the economic aspect is seen based on the results of qualitative and quantitative analysis of the condition of forest resources and the implementation strategy is carried out using a SWOT analysis. The results of the study reveal that the economic aspect of forest resources is that the forest is managed as a producer of water and environmental services for the economic sustainability of downstream communities in Sidrap Regency. Meanwhile, the management implementation strategy refers to the management of protected forest areas for the main purpose of producing water and other non-timber forest products. Another strategy is to develop cross-district cooperation in the management of forest resources for water production, develop cultural and tudang sipulung conservation programs related to forest function preservation, develop forestry institutions at the local level according to the values ​​that exist in the local community and increase public understanding. on the function of forest water management. Sustainable SDH management in Sidrap Regency needs to apply locality approaches. Restructuring of district forestry institutions should also be pursued in order to create intensive coordination between sectors, especially between the forestry sector and sectors related to water.